2007
DOI: 10.1111/j.1365-2133.2007.08033.x
|View full text |Cite
|
Sign up to set email alerts
|

Stromelysin-3 expression in the differential diagnosis of dermatofibroma and dermatofibrosarcoma protuberans: comparison with factor XIIIa and CD34

Abstract: Immunohistochemical staining with a commercial anti-ST3 antibody can be successfully carried out in routine dermatopathology. We confirmed that ST3 is a positive marker for DF and that ST3 staining might be more reliable than factor XIIIa staining in differential diagnosis of DF and DFSP. As the present study showed that ST3 was not absolutely negative in all cases of DFSP, the combination with CD34 immunostaining could make the distinction more reliable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 25 publications
4
45
0
Order By: Relevance
“…In the particular case of DFSP, the definitive diagnosis is usually established on the basis of routine histopathological and immunohistochemical features. Neoplastic cells usually express CD34 antigen and APOD1 and are negative for factor XIIIa, stromelysin III and D2-40 (Cribier et al, 2002;Kim et al, 2007;Bandarchi et al, 2010). In this neoplasm a pathogenic and specific translocation t(17;22)(q22;q13) (COL1A1/ PDGFB) has been well-characterized (Pedeutour et al, 1993(Pedeutour et al, , 1995(Pedeutour et al, , 1996Naeem et al, 1995).…”
Section: Comparison Between Rt-pcr and Fish Techniquesmentioning
confidence: 93%
“…In the particular case of DFSP, the definitive diagnosis is usually established on the basis of routine histopathological and immunohistochemical features. Neoplastic cells usually express CD34 antigen and APOD1 and are negative for factor XIIIa, stromelysin III and D2-40 (Cribier et al, 2002;Kim et al, 2007;Bandarchi et al, 2010). In this neoplasm a pathogenic and specific translocation t(17;22)(q22;q13) (COL1A1/ PDGFB) has been well-characterized (Pedeutour et al, 1993(Pedeutour et al, , 1995(Pedeutour et al, , 1996Naeem et al, 1995).…”
Section: Comparison Between Rt-pcr and Fish Techniquesmentioning
confidence: 93%
“…In others studies, the sensitivity of this test varied from 84 to 100%. [26][27][28] The test was less successful in differentiating dermatofibrosarcoma protuberans from its main differential diagnoses, including 19 (63%) undifferentiated sarcomas, 6 (85%) myxofibrosarcomas, and 4 (100%) spindle cell lipomas stained positive for CD34. Kim et al 28 found CD34 to be a valuable stain for differentiating between dermatofibrosarcoma protuberans and dermatofibroma, and reported a specificity of 83%.…”
Section: Initial Diagnosismentioning
confidence: 99%
“…Immunohistochemical stains are required to differentiate dermatofibroma (DF), DFSP and other fibrous tumours. CD34, factor XIIIa, stromelysin-3 (ST3) and apolipoprotein D (Apo D) are some of the important stains used [7]. CD34 positivity is seen in most cases of DFSP.…”
Section: Discussionmentioning
confidence: 99%